The Native Police of Queensland - Richards, Jonathan (History compass, 2008)
The European colonisation of Queensland largely depended on the armed and mounted men of the Native Police - a brutal force which killed many Indigenous people on the frontier. Detachments of mounted Aboriginal troopers led by European officers would surround Aboriginal camps and fire into them at dawn, killing men, women and children. The bodies were often burned to destroy the evidence. Jonathan Richards has spent many years researching this controversial and distressing subject, finding his way through the secrecy, misinformation and supposed ‘lost’ files. In this article, based on the first comprehensive study of the force's history in Queensland, he argues that the Native Police was a classic example of ‘divide and rule’ practices. This colonising tactic, successfully used by the British and other imperial powers, was approved by government and by most European settlers.